The effects of COVID-19 on patients with systemic arterial hypertension: a systematic review (Research, Society and Development, 2022)
Objective: The research focuses on addressing the importance of SAH as a potential risk factor in patients affected by COVID-19. Methods: The methodology adopted in the present study was based on a systematic literature review, in its qualitative sphere, the result of studies based on 10 scientific articles, once listed for the formation of this study. Results: The total number of people with SAH in the present sample is 5,234 with a mean age of 60 years. The most used drugs were Calcium Channel Antagonists, Angiotensin Receptor Beta Blockers (ARB), Angiotensin Converting Enzyme Inhibitors (ACEI) and Alpha Blockers. In this meander, the results showed that the use of (ACEI) and Angiotensin Receptor Blockers (ARB), compared to non-ACEI/ARB, do not worsen COVID-19. Current evidence suggests that SARIs should be continued in the case of patients infected with the virus. Some studies have reported that SAH patients are at greater risk of having a more serious condition if they test positive for the new strain of coronavirus. Conclusion: The present research concluded that hypertensive patients with COVID-19 are at greater risk of worsening the disease than non-hypertensive patients. These findings reveal that the worsening of the condition of hypertensive patients and those with COVID-19 is due to the renin-angiotensin-aldosterone system (RAAS), which ends up favoring the binding of the virus to the body of these individuals.